Strategic management accounting practices: a literature review and opportunity for future research - Md. Mamunur Rashid; Md. Mohobbot Ali; Dewan Mahboob Hossain (Asian Journal of Accounting Research, 2020)
The purpose of this study is to review the empirical studies that have focused on the adoption, benefits and contingencies of strategic management accounting (SMA) practices and the effects of adoption on firm performance.The study has highlighted empirical studies conducted on SMA practices in the context of both developed [1] and developing economies. In reviewing the literature, the study focuses on the findings of developed economy separately from that of developing economy to get more insight into the differences in the practices of the two set of economies. Based on the review, avenues for future research studies are outlined.The review of extant literature reveals that several SMA techniques such as competitor accounting, strategic pricing, benchmarking and customer accounting have been highly or moderately adopted in several developed countries while majority of other techniques remained at the bottom line of the adoption status. However, the review demonstrates substantial differences in the SMA practices between the two set of economies in terms of the level of adoption, contingent factors and the effects of adoption.The study attempts to focus on empirical studies that have concentrated exclusively on SMA practices. The adoption status, benefits derived, contingent factors affecting the adoption decision and the effect of adopting a package of SMA techniques on several aspects of firm performance are presented in the context of both developed and developing economies.